Study of adherence kinetics of Escherichia coli on cotton knitted fabrics. Issue 3 (3rd July 2019) - Bajpai, S.; Bajpai, Vidushi; Dey, Apurba; Ghosh, Subrata; Jha, M.K.
ABSTRACT: Textile materials especially those used in hospitals, food industry, sportswear, infant wears, bath rooms, home and kitchen are susceptible to the attacks of various harmful microorganisms present in the environment. The study of bacterial adherence on such microbial infested fabrics is a pre-requisite to develop suitable antimicrobial finished articles. This work therefore aimed towards studying bacterial adherence of Escherichia coli on 100% cotton knitted fabrics. Lowry's method was used to quantify the adherent bacterial cells to the fabric. The adherence was studied and compared for three differently pre-treated fabrics. The effect of agitation time and pH on adherence was also investigated. The kinetic data were analysed by first-order kinetics using Lagergren equation. The Gibb's free energy for the adherence process was found to be −3.753 kJ mol −1 . The mechanism of adherence was understood with the help of Scanning Electron Microscope (SEM) and Fourier transform infra-red (FTIR) spectroscopy. SEM micrograph suggests that adherent bacteria did not uniformly cover the entire surface of the cotton fabric. They were found more near the creases present on cotton indicating that surface morphology plays significant role in bacterial adherence. Comparing FTIR spectra of E. coli and cotton fabric suggests that hydrophilicity promotes the bacterial adherence.